Kajian Puisi-Puisi Pernyataan Rindu Karya M. Hanfanaraya Menggunakan Pendekatan Semiotika - Dudi Supriadi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Semiotics is a study of signs. The poems of Pengagum Rindu by M. Hanfanaraya contains elements of semiotics such as icons, indexes, and symbols. The purpose of the study was to identify and analyze semiotics in the poems of Pengagum Rindu by M. Hanfanaraya. The scope of the research is the study of literary criticism, namely the study of semiotics. The limitation of the problem in this research is that the author takes all aspects of semiotics on the types of signs such as icons, indexes, and symbols. There are two sources of data, namely primary data sources and secondary data sources. This type of research is a qualitative research using a descriptive qualitative approach. Data collection techniques used are hermeneutic and documentation techniques. The data analysis technique uses text analysis techniques. The results of the research that were found were (9) the symbol aspect was found as many as 1(one) data consisting of words, combinations of words, and phrases.